The role of ideas in education politics: using discourse analysis to understand barriers to reform in multiethnic cities - Sidney, Mara S. (2002)
This article examines how the presence of multiple racial and ethnic groups complicates education politics. It suggests that to fully understand the multiethnic political terrain, we need to study how diverse groups understand their interests, and it proposes that discourse analysis offers an effective method for doing so. In four cities under study, coalitions across racial minority groups did not emerge to pursue education reform, despite shared dissatisfaction with the schools. Analysis of interview data shows a complex arena of problem definitions and assessments of reforms, one so infused with issues of race and ethnicity that groups agreeing on some elements of "the education problem" may be kept apart by their differing interpretations of its racial dimensions. The findings suggest that divergent ideas about how race intersects with education problems and solutions pose barriers to collective action and meaningful education reform in multiethnic cities. - Reproduced.
Keywords: Education